Management of Kempo Sport Department Achievements Development Program in Belu Regency, East Nusa Tenggara - Seran, Yohanes Arka Maria; Rumini, Rumini; Soegiyanto, Soegiyanto (Journal of Physical Education and Sports, 2019)
The objectives of the study are: (1) Context covers the background, vision and mission of the development program, (2) Input covers the availability of Human Resources (HR), the feasibility of facilities and infrastructure the funding sources for the implementation of the Belu East Nusa Tenggara Kempo achievement development program, (3) Process includes the implementation of training programs, trainer performance, transportation and coordination between elements, (4) Product includes the achievements of Kempo, Belu East Nusa Tenggara. The results of this study are (1) Context teaches the vision and mission and goals of the Belu district of NTT. (2) Input Kempo has good human resources, the feasibility of facilities and infrastructure is very good, and funding sources that still have limitations. (3) Process the program implementation of the training is the right of the trainer and the training staff. Recruitment of athletes is also part of the coach's rights but there is input from the board because the board is also involved in the recruitment. Transportation and coordination have been very well carried out in the Belu district of East Nusa Tenggara. (4) The Product of the Kempo fostering program is an achievement, for Belu NTT Kempo achievement is good but to maintain the champion is still not stable in 2015-2019. This study concludes that from the aspect of context, input, the process is very good, while the Belu NTT product is a good achievement because Belu NTT is often following the championship in Indonesia, but to maintain the champion is still not stable.